Translation Techniques of Swear Words Found in Colleen Hoover's Novel Entitled "It Ends with Us" - Putri, Nurul Assyifa; Ardi, Havid (English Language and Literature, 2024)
This research analyzed the types of swear words and the translation techniques of swear words that found in a translated novel by Colleen Hoover entitled It Ends With Us into Bahasa Indonesia. This research used descriptive qualitative method to collect the data. The researcher used the theory by Anderson (1992) to analyze types of swear words and the theory by Molina & Albir (2000) to analyze translation techniques of swear words. The researcher found all types of swear words such as expletive swearing, abusive swearing, humorous swearing and auxiliary swearing, the most type that found is expletive swea. Then the researcher also found nine types of translation techniques of swear words such as adaptation, compensation, amplification, established equivalent, literal translation, linguisric amplification, linguistic compression, transposition and modulation, the most techniqu that found is established equivalent.